Disparities in the Diagnosis of Hypertrophic Obstructive Cardiomyopathy: A Narrative Review of Current Literature - Joseph Burns; Philippe Jean-Pierre (Cardiology Research and Practice)
Hypertrophic obstructive cardiomyopathy (HOCM) is a disorder of abnormal thickening of the myocardium that affects 0.2% of the population. HOCM is a frequently implicated cause of sudden cardiac death (SCD) in young athletes. In this manner, this condition has the capacity for tremendous emotional, social, financial, and medical burdens for families and communities across the country. Multiple factors including genetics and hormonal elements are believed to play a role in the development of this cardiomyopathy. HOCM is an autosomal dominant trait with variable expressivity. It is associated with several genetic changes in the myosin heavy chain genes. Current treatment includes optimization of cardiac risk factors and medical management with beta-adrenergic blockade with definitive treatment of surgical intervention to reduce cardiac workload. The demographic most likely to be diagnosed with HOCM based upon clinical registry data is Caucasian boys and men. However, a growing body of data supports increased prevalence in African American populations and percentages equal to, if not higher than, Caucasian males in Hispanic populations. Similarly, males of African American ethnicity that participate in basketball are the most likely demographic to be affected by HOCM based on the data available from the National Collegiate Athletic Association (NCAA). Further, though rates of diagnosis may be up to 1.5 times higher in males than in females, an increasing number of studies demonstrate an increased prevalence of HOCM in females, often presenting with worse symptoms and an increased incidence of disease progression. Similarly, data suggest that age of diagnosis is associated with various prognostic factors including annual mortality. In addition, consideration of the social determinants of health undoubtedly impacts the rate of diagnosis, access to care, and HOCM-related complications in underserved populations. Effective screening including auscultation and electrocardiography (EKG) with confirmatory echocardiography in these communities supports equitable surveillance and management of HOCM.